2011
DOI: 10.2527/jas.2011-4067
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tropical adaptation on plasma concentrations of insulin-like growth factor-I in purebred and crossbred beef cattle1

Abstract: In an effort to determine whether tropical adaptation influences circulating concentrations of the growth-related hormone IGF-I, 3-breed diallel matings were conducted using temperate Bos taurus (Angus), tropical Bos indicus (Brahman), and tropical Bos taurus (Romosinuano). Purebred Angus, Braham, and Romosinuano and crossbred Angus-Braham, Angus-Romosinuano, and Braham-Romosinuano heifers and steers were evaluated in 2 separate calf crops from 2003 and 2004. Blood samples were obtained from 10 heifers of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several studies have shown that blood concentrations of IGF-I are generally low in early lactation, when many cows experience a negative energy balance, but then increase as lactation progresses and positive energy balance is restored (Lucy, 2000). It therefore appears that the Sanga breed is better adapted to tropical environmental conditions (poor diets, high temperatures) than the Friesian-Sanga crossbred (Sottie et al, 2009), as seen in comparisons of Brahman, Romosinuano and Angus breeds (Alvarez et al, 2000;Obeidat et al, 2002;Spicer et al, 2002;Caldwell et al, 2011). However, the present study also confirmed an earlier report by Darfour-Oduro et al (2010) that the two breeds differ greatly in milk production, and thus their output of energy through this important aspect of productivity.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown that blood concentrations of IGF-I are generally low in early lactation, when many cows experience a negative energy balance, but then increase as lactation progresses and positive energy balance is restored (Lucy, 2000). It therefore appears that the Sanga breed is better adapted to tropical environmental conditions (poor diets, high temperatures) than the Friesian-Sanga crossbred (Sottie et al, 2009), as seen in comparisons of Brahman, Romosinuano and Angus breeds (Alvarez et al, 2000;Obeidat et al, 2002;Spicer et al, 2002;Caldwell et al, 2011). However, the present study also confirmed an earlier report by Darfour-Oduro et al (2010) that the two breeds differ greatly in milk production, and thus their output of energy through this important aspect of productivity.…”
Section: Discussionmentioning
confidence: 89%
“…In the following analysis, a reference dealing with two or more categories was counted only once in the category it most suited. Of the 100, the main topics of the studies broke down as follows: There were 35 studies of breeds and breeding (19)(20)(21)(22)(23)(24); 32 studies of feeds, nutrition, or pastures (25)(26)(27)(28)(29); 11 studies of parasites and disease resistance (30)(31)(32)(33)(34); 10 studies of genes or genomes (35)(36)(37)(38)(39)(40); 8 studies of the environment, including mitigation, farming systems, and biofuels (41)(42)(43)(44)(45); and 4 studies of reproduction (46,47). Of these 100 studies, there were 15 studies that took into account heat; 5 in which heat was the main focus; and 10 in which either heat was the minor focus or the traits studied were surrogates for heat, such as coat characteristics (48)(49)(50)(51).…”
Section: Tropical Cattle Adaptationmentioning
confidence: 99%